2011
DOI: 10.1128/iai.05371-11
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking Affects Bacterial Acquisition and Colonization in Oral Biofilms

Abstract: Recent evidence suggests that smoking affects the composition of the disease-associated subgingival biofilm, yet little is known about its effects during the formation of this biofilm. The present investigation was undertaken to examine the contributions of smoking to the composition and proinflammatory characteristics of the biofilm during de novo plaque formation. Marginal and subgingival plaque and gingival crevicular fluid samples were collected from 15 current smokers and from 15 individuals who had never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
177
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(211 citation statements)
references
References 56 publications
23
177
1
10
Order By: Relevance
“…Loss of beneficial oral species due to smoking can lead to pathogen colonization and ultimately to disease; this contention is strongly supported by the well-established role of smoking in the onset and progression of periodontitis (Nociti et al, 2015). Previous studies have shown alterations in the abundance of selected oral bacteria in smokers compared with non-smokers (Colman et al, 1976;Ertel et al, 1991;Charlson et al, 2010;Kumar et al, 2011;Hugoson et al, 2012;Morris et al, 2013;Belstrom et al, 2014;Mason et al, 2015); however, results across these studies are largely inconsistent, possibly due to small sample sizes in some, use of different sampling sites in the mouth and use of different laboratory methodologies, some of which impose limitations on bacterial profiling.…”
Section: Introductionmentioning
confidence: 74%
“…Loss of beneficial oral species due to smoking can lead to pathogen colonization and ultimately to disease; this contention is strongly supported by the well-established role of smoking in the onset and progression of periodontitis (Nociti et al, 2015). Previous studies have shown alterations in the abundance of selected oral bacteria in smokers compared with non-smokers (Colman et al, 1976;Ertel et al, 1991;Charlson et al, 2010;Kumar et al, 2011;Hugoson et al, 2012;Morris et al, 2013;Belstrom et al, 2014;Mason et al, 2015); however, results across these studies are largely inconsistent, possibly due to small sample sizes in some, use of different sampling sites in the mouth and use of different laboratory methodologies, some of which impose limitations on bacterial profiling.…”
Section: Introductionmentioning
confidence: 74%
“…Diversity colonies were found more in smokers than nonsmokers. Thus, microbial communities showed lower stability after 7 days in smokers than non-smokers [14].…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al showed that there were differences in the number of bacterial colonies in smokers and non-smokers were taken from the margin, subgingival plaque and gingival sulcus fluids [14]. Differences in the number of bacterial colonies in smokers due to exposure to tobacco affect the bacterial composition of the plaque.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasoconstriction of blood vessels leads to reduced clinical signs and suppressed clinical expression of disease [11] .A study done by Kemal et al showed that smoking significantly increased Gingival crevicular fluid flow/volume when compared to non-smokers. Purnima et al conducted a study with Gingival crevicular fluid, marginal and sub gingival plaque that revealed early acquisition and colonization of oral biofilm in smokers [12] .…”
Section: Discussionmentioning
confidence: 99%